Estimation of the prevalence and distribution of HPV genotypes and identification of related risk factors among Turkish women - Kulhan, Mehmet; Kulhan, Nur G.; Seven, Yasemin; Nayki, Umit A.; Nayki, Cenk; Ata, Nahit; Ulug, Pasa (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : The present study aims to estimate the prevalence and distribution of HPV genotypes and identify related risk factors among Turkish women. Material and methods : 11 624 Turkish women attending our gynaecological clinic and expressing a desire for access to cervical cancer screening were assessed during the years 2014–2016. Cervical specimens were collected and transported using the HC2 HPV DNA Collection Device (consisting of a cervical brush and digene Specimen Transport Medium). Results : Among these 11 624 individuals, positive HPV test results were obtained for 325 (2.79%), and negative results were observed for 11 299 (97.2%). The vast majority of patients were between the 3rd and 5th decades and the mean age of the patients was 44 ±9.12 (range 27–66). Among the HPV-positive women, 205 were positive for a single HPV type (205/325 = 63.1% of HPV infections; 205/11624 = 1.76% of all samples) and 120 were positive for multiple types (120/325 = 36.9% of HPV infections; 120/11624 = 1.03% of all samples). The four most prevalent high-risk types were HPV 16, 31, 51 and 52, with frequencies of 11.25%, 7.83%, 6.06% and 3.16%, respectively. Conclusions : There appears to be geographic variation in the distribution of HPV genotypes. In this study, the four most prevalent high-risk types were HPV 16, 31, 51 and 52, with frequencies of 11.25%, 7.83%, 6.06% and 3.16%, respectively.